Pengaruh Kesadaran Dan Persepsi Masyarakat Terhadap Kepatuhan Membayar PBB Di Desa Jatirejo Kecamatan Girimarto Kabupaten Wonogiri Tahun 2016 - Susanto, Pajar; , Dr. Wafrotur Rohmah (2016)
The purpose of this study was to determine the effect of awareness and public perception of their financial obligations to pay PBB compliance. This research is quantitative research with associative approach that examine the relationship between variables. The study population was the whole community in the village Jatirejo Girimarto District of Wonogiri who owns a home and land that became the PBB taxpayer as many as 926 people. Samples taken as many as 93 PBB taxpayers. The sampling technique using simple random sampling. The data collection technique using a questionnaire that had been tested in advance and tested for validity and reliability test. Data analysis technique used is multiple regression analysis, t-test, F, R2 test, as well as the relative contribution and effective. Results of data analysis obtained regression equation: Y = 2.081 + 0,478.X1 + 0,433.X¬2. This equation shows that the awareness of paying taxes and the effect on the public perception of compliance to pay PBB. The conclusions drawn are: (1) Awareness pay taxes positive effect on compliance with the PBB pay. The test results obtained tcount t> t table (5.772> ) = 5%.1.980) at 5% significance level and significance < 0,05 about 0,000. (2) The perception of individual tax liabilities (partial) positive effect on compliance with the PBB pay. The test results obtained tcount t> t table (4.185> ) = 5%.1.980) at 5% significance level. and significance < 0,05 about 0,000. (3) Awareness and perception pay taxes on tax obligations together (simultaneously) positive effect on compliance with the PBB pay. F test results obtained F count> F table (71.016> ) = 5%.3.07) at 5% significance level and significance < 0,05 about 0,000. (4) variable X1 gives the relative contribution of 59,6% and the effective contribution of 36,5%. Variable X2 gives the relative contribution of 40,4% and the effective contribution of 24,7%. The coefficient of determination (R2) or total contribution of variable pay taxes consciousness and perception of compliance with tax obligations towards the PBB pay is 61.2%, while 38.8% is influenced by other variables not examined.